Peran BK dalam Memberikan Pemahaman Pendidikan Seks kepada Siswa - Ahmad Zulfahmi Muwafiq Billah; Imroatul Hayyu Erfantinni (ILIN Institute, 2021)
The purpose of this paper is to understand the roles of BK in order to teach students sexual understanding. The paper will focus on the teacher’s methods in delivering sex education material. The methodology that used in this paper is literature review that collecting the data from various literature sources related to this paper topic, including some previous studies that have been conducted. The researcher used theoretical frame from several experts about sex education and some BK’s attempts that possible to be conducted in teaching sexuality. The finding of this research revealed that BK teachers could utilize various media and activities to deliver sex education material. It gave positive results on students whether in individual or group counseling, offline or online counseling. This result showed and proved the effectiveness of BK’s service on giving an understanding of sex education.